Evaluasi Kelayakan Finansial Usaha Peternakan dan Pengembangan Biogas: Studi Kasus Desa Suntenjaya, Bandung - Maeanti, Resty F.; Fauzi, Akhmad; Istiqomah, Asti (Jurnal Ekonomi dan Pembangunan Indonesia, 2013)
This study aims to evaluate the feasibility of biogas project in Suntenjaya Village, Bandung and identify factors that affect revenues, environment and wider economic benefit of the project, using benefit cost analysis, multiple regression, and descriptive analysis. The results show that biogas project is feasible to be developed. Variables that significantly influence on the biogas project are total amount of poultry's waste, total amount of water, and labor. Economic impact of biogas from employment is 1.96%. Furthermore, fuel cost savings of biogas is IDR1,406,160. Environmental impact shows that mostly of cow farmer agree that biogas development project give positive impacts to environment.